2022
DOI: 10.3390/children9101464
|View full text |Cite
|
Sign up to set email alerts
|

Change on the Circulation of Respiratory Viruses and Pediatric Healthcare Utilization during the COVID-19 Pandemic in Asturias, Northern Spain

Abstract: (1) Background: The COVID-19 pandemic and the implementation of restrictions and nonpharmaceutical interventions (NPIs) changed the trends in respiratory viral circulation and the pattern in pediatric healthcare utilization; (2) Methods: A retrospective, multicenter observational study designed to analyze the impact of the pandemic on pediatric healthcare utilization and the viral circulation pattern in children in a region in Northern Spain was carried out. Viral diagnostics data from all nasal or pharyngeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Specifically, between CW 51/2020 and CW 21/2021, a total of 2382 combined SARS-CoV-2/FLU/RSV tests resulted in zero detections of influenza virus and RSV. Our data are thus in accordance with a recent study from Greece, which observed no detection of influenza virus in 2021 [ 49 ], and a study from Spain that reported no influenza or RSV detections in children between CW 14/2020 and CW 19/2021 [ 50 ]. Similarly, a study from Madagascar reported no detection of influenza virus and reduced RSV detections in the cold season 2020/2021 [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, between CW 51/2020 and CW 21/2021, a total of 2382 combined SARS-CoV-2/FLU/RSV tests resulted in zero detections of influenza virus and RSV. Our data are thus in accordance with a recent study from Greece, which observed no detection of influenza virus in 2021 [ 49 ], and a study from Spain that reported no influenza or RSV detections in children between CW 14/2020 and CW 19/2021 [ 50 ]. Similarly, a study from Madagascar reported no detection of influenza virus and reduced RSV detections in the cold season 2020/2021 [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…These pandemic measures likely helped avoid infection with other respiratory pathogens. For example, in a study conducted in Northern Spain, the usual seasonal respiratory viruses, such as RSV, Rhino/Entero, HMPV, PIV, Flu, CoV, and AdVs, were found nearly absent in the pediatric population between 2018-2019 and 2020-2021 [10]. In Mexico, the national indicators showed a decreased incidence of Flu infection after the implementation of NPIs on March 23, 2020 [11].…”
Section: Introductionmentioning
confidence: 99%